CROWDSOURCING TASK PLATFORM FOR SOCIAL NETWORK - Prasetya - NIM : 13514003 , Davin
Crowdsourcing is a powerful way to process and collect data that needs human’s logic and perception. Crowdsourcing can take part in many hard to compute problems such as data entry, multimedia transcriptions and many case of artificial intelligence. While this is a powerful approach, crowdsourcing needs a relatively large marketplace to works optimum. In context of Indonesia, we hardly hear about microtask crowdsourcing even though there are some marketplace like poin-web.co.id. In this paper, we propose a social network for crowdsourcing marketplace to penetrate the market. People tends to waste most of their time on social network and game rather than other mobile application in case of mobile usage. The idea is to make crowdsourcing as a filler while people are using social networks like waiting for a chat or scrolling the timeline. And by applying microtask as the task, people will not have much burden on doing the task. On the other hand, he/she will get additional income. We implemented LINE as a basis of our social network marketplace. LINE does provide the most interactive way of provide message. Additionally, the user of LINE in Indonesia is growing in a fast pace. Platform is designed to facilitate common type of task that used in crowdsourcing. We conduct an experiment focused on worker’s effectivity and ease of use. The result of the experiment proved that all the functional requirement has been met. Platform facilitate various task such as image classification, product comparison, image moderation, transcription, collecting data, sentiment analysis and survey. Quality control test showed that voting system provide a better answer with cost of including larger amount of workers. By using usability testing as a basis of ease of use evaluation, we received good feedbacks as worker responded the task quite fast, did not feel confused on using the platform and 81.8% did not feel disturbed while using LINE. The amount of time needed for a task to finish also relatively fast.